xxxxxxxxxx
G = (N, T, P, S)
N = {Satz, Nominalphrase, Verbalphrase, Eigenname, Artikel, Substantiv, Verb}
T = {Susanne, Katze, Pferd, Heu, Buch, der, die, das, jagt, frisst, liest}
P = {(Satz -> Nominalphrase Verbalphrase .),
(Nominalphrase -> Eigenname | Artikel Substantiv),
(Verbalphrase -> Verb | Verb Nominalphrase),
(Eigenname -> Susanne),
(Substantiv -> Katze | Pferd | Heu | Buch),
(Artikel -> der | die | das),
(Verb -> jagt | frisst | liest)}.
S = Satz
xxxxxxxxxx
G = (N, T, P, S)
N = {Satz, Nominalphrase, Verbalphrase, Eigenname, Artikel, Substantiv, Verb}
T = {Susanne, Katze, Pferd, Heu, Buch, der, die, das, jagt, frisst, liest}
P = {(Satz -> Nominalphrase Verbalphrase .),
(Nominalphrase -> Eigenname | Artikel Substantiv),
(Verbalphrase -> Verb | Verb Nominalphrase),
(Eigenname -> Susanne),
(Substantiv -> Katze | Pferd | Heu | Buch),
(Artikel -> der | die | das),
(Verb -> jagt | frisst | liest)}.
S = Satz